Alkaloids with neuroprotective effects from the leaves of Isatis indigotica collected in the Anhui Province, China. (May 2018) - Liu, Si-Fan; Zhang, Ying-Ying; Zhou, Le; Lin, Bin; Huang, Xiao-Xiao; Wang, Xiao-Bo; Song, Shao-Jiang
Abstract: Six undescribed alkaloids, indiforine A-F, together with four known ones, were isolated from the leaves of Isatis indigotica Fortune. Their structures were elucidated on the basis of extensive spectroscopic analyses. The absolute configurations of indiforine A and B were determined by comparison of the experimental and calculated electronic circular dichroism spectra, as well as experimental and calculated optical rotations. The isolated alkaloids were evaluated for their neuroprotective activities against H2 O2 -induced cell injury in human neuroblastoma SH-SY5Y cells. The results showed that in H2 O2 -induced SH-SY5Y cell injury models, indiforine A and B exhibited potent neuroprotective activities. Further investigation of the most potent indiforine A by Hoechst 33258 staining and Annexin V/PI analysis demonstrated that it could protect SH-SY5Y cells from oxidative damage through inhibiting cell apoptosis. Graphical abstract: Six undescribed alkaloids, Indiforine A-F, were isolated from Isatis indigotica, which were evaluated for their neuroprotective activities against H2 O2 -induced cell injury in human neuroblastoma SH-SY5Y cells.Image 1 Highlights: Six undescribed alkaloids were isolated from the leaves of Isatis indigotica. Calculated methods were used to determine the absolute configurations. Indiforine A exhibited neuroprotective effect against SH-SY5Y cell injury. Mechanism study revealed indiforine A elicited activity via inhibiting apoptosis.